THE EFFECT OF ADDITIVE COMBINATION AND Azotobacter sp. TOWARDS Glycine max. L. GROWTH - Yunia Vella Alfani; Pudjawati Suryatmana; Ade Setiawan (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2019)
This study was aimed at determining the increasing of growth and production of soybean crops by giving Azotobacter sp. and additive materials such as coconut water, molasses, and bran. This research was conducted on Januari 2018 to April 2018 at Ciparanje Experimental Field Faculty of Agriculture. Universitas Padjadjaran, Jatinangor, Sumedang, West Java Province, on ± 774 meters above sea level (asl) using single factor randomized block design with 10 treatments; Azotobacter sp. and additive materials combination such as coconut water, molasses, and bran in three repetitions. The observations on the parameters observed in the final vegetative phase were on plant height, chlorophyll content, and population of Azotobacter sp. using Total Plate Count (TPC) method.The results show that the application of combination additives materials and Azotobacter sp. effect on populations Azotobacter sp., chlorophyll content, plant height and number of soybean pods (Glycine max L.). Application of coconut water independently, water added with Azotobacter sp., and combination of additive with Azotobacter sp. can give the best effect to the content of chlorophyll, plant height, and soybean crops components (Glycine max. L.).PENGARUH KOMBINASI BAHAN ADITIF DAN Azotobacter sp. TERHADAP PERTUMBUHAN Glycine max. L.Penelitian ini bertujuan untuk mengetahui pertumbuhan dan produksi tanaman kedelai dengan memberikan Azotobacter sp. dan aditif air kelapa, molase, serta dedak. Penelitian ini dilaksanakan pada Januari 2018-April 2018 di Kebun Percobaan Ciparanje Fakultas Pertanian Universitas Padjadjaran, Jawa Barat pada ± 774 meter di atas permukaan laut (dpl). Penelitian ini menggunakan rancangan acak kelompok dengan 10 perlakuan pemberian Azotobacter sp. dan aditif air kelapa, molase, serta dedak dengan tiga ulangan. Pengamatan terhadap parameter yang diamati pada fase vegetatif akhir yaitu tinggi tanaman, kandungan klorofil, dan populasi Azotobacter sp. dengan metode Total Plate Count (TPC). Hasil penelitian menunjukkan aplikasi kombinasi bahan aditif dan penambahan pupuk hayati Azotobacter sp. berpengaruh terhadap populasi Azotobacter sp., kadar klorofil, tinggi tanaman dan jumlah polong tanaman kedelai (Glycine max L.). Aplikasi air kelapa secara mandiri, air kelapa yang ditambahkan dengan Azotobacter sp., dan kombinasi bahan aditif dengan Azotobacter sp. dapat memberikan pengaruh terbaik terhadap kandungan klorofil, tinggi tanaman, dan komponen hasil tanaman kedelai (Glycine max. L.).